Examination of the Concept of Social Stratification in the Lecture Theme of Kinship System in the Department of Anthropology Education UNM - Dimas Ario Sumilih; Atma Ras (Universitas Negeri Makassar, 2025)
AThis research aims to examine the concept of social stratification in the theme of kinship system lectures taught through the “Kinship System and Social Organization” course at the UNM Department of Anthropology Education. The method used was Systematic Literature Review (SLR) by reviewing journal articles in the last 10 years to identify findings related to social stratification and kinship. The research findings show that the integration of sociology and anthropology perspectives provides a richer multidisciplinary understanding, particularly in the context of teaching this theme in anthropology education. Teaching based on local contexts, such as the Balinese caste system, Minangkabau matrilineal, and Bugis-Makassar patrilineal, is relevant for strengthening students' understanding. This research bridges the gap in the teaching of social stratification that still lacks the integration of multidisciplinary approaches, especially in linking the structural aspects of sociology with the cultural and symbolic norms that are the main focus of anthropology. In conclusion, the integration of theory and practical application in teaching can contribute significantly to the development of anthropology education curriculum at UNM. With this approach, students can understand the relevance of social stratification more critically and contextually in Indonesian society.